Isolated subclinical right ventricle systolic dysfunction in patients after liver transplantation - Çeliker Güler, Emel; Omaygenç, Mehmet Onur; Naki, Deniz Dilan; Yazar, Arzu; Karaca, İbrahim Oğuz; Korkut, Esin (MDPI, 2023)
Although hemodynamic alterations in end-stage liver disease (ESLD) and its association with porto-pulmonary hypertension have been well-established, the long-term effects of ESLD on RV systolic function in patients without porto-pulmonary hypertension remain disregarded. Here we aimed to assess the long-term effect of ESLD on RV function and its relationship with the use of NSBBs and clinical, laboratory and imaging parameters in end-stage liver disease. The use of NSBBs is still controversial due to concerns about reduced cardiac contractility and the possibility of increased mortality. Thirty-four liver transplant recipients were included. Demographic characteristics, laboratory and baseline echocardiography measures were obtained. Patients were recalled for transthoracic echocardiographic evaluation after transplantation. Right ventricle dysfunction was identified by having at least one value below the reference levels of RV S', or TAPSE. Isolated subclinical RV dysfunction was observed at 20.6% of the sample population. The present study demonstrates hemodynamic circulation in cirrhosis and increased preload and afterload might have long-term effects on RV function, even the lack of porto-pulmonary hypertension. These findings underline the significance of cardiac function follow-up in cirrhotic patients after transplantation. In this study, patients treated with propranolol seemed to have better RV function and less gastrointestinal bleeding. We speculated that preoperative propranolol treatment might help preserve RV function by providing RAS suppression, improving endothelial function and hyperdynamic circulation seen in ESLD. This potential protective relationship between the use of propranolol and RV function might improve mortality or graft-failure during OLT and after liver transplantation in patients with cirrhosis.
Keywords: End-Stage Chronic Liver Disease; Liver Transplantation; Heart Failure; Right Ventricle Function; Propranolol